Імперативи розвитку мультимодальних перевезень у відповідності з тенденціями трансформаційних зрушень національного господарства в умовах євроінтеграції - Gurnak, Vitaly; Khomenko, Inna; Volynets, Lyudmila (Dr. Viktor Koval, 2018)
Introduction Despite the existing potential of freight capacity of rail, sea and river transport, their interaction is still in need of improvement. Given the high growth rates of international container traffic, Ukraine's transport infrastructure requires immediate modernization and investment in the technical and economic condition in a context of intense competition with foreign transport companies and ports. Aim and tasks is to identify and substantiate the possibilities of improving the mechanism of organization of multimodal transportation in accordance with the latest trends and ensuring the further sustainable development of multimodal cargo transportation, etc. Research results. It established that at the present stage, multimodal transport covers not only technological aspects of coordinated work of different types of transport, but also concerns economic, organizational and legal provision of transport process, efficient functioning of transport infrastructure, optimal use of vehicles and cargo units during traffic flow. The article investigates the theoretical basis of multimodal transport, defines the general principles of the multimodal transportation system functioning, raises the grounds for the possible development of multimodal transport and improvement of the transport industry in Ukraine, as well as increasing the competitiveness of domestic enterprises. The methodical provisions of multimodal transport development in Ukraine offered. Conclusion. Today it is necessary to introduce new principles of formation and coordination of state policy in the field of transport, creation of conditions for ensuring control over the quality of performance of the functions of the relevant executive authorities. Organization of multimodal transport, which will be carried out by a single operator on a single transport document and through a freight rate, will increase the quality of transport and logistic services, will ensure a high level of reliability and security of international freight delivery chains.